Geometrical analysis of the largest oval dome in the world - Giuseppa Novello; Paolo Piumatti (Disegnare con, 2012)
The dome of the Sanctuary of Vicoforte, the largest oval masonry dome in the world, is an exceptional expression of building technique for its shape and dimension. This study wants to add information about the geometrical conception of the dome using the modern modeling possibilities based on recent laser scanner survey. In particular it integrates the analysis of the archival drawings and the 3D survey of the dome in order to investigate the geometrical shape of the temporary centrings used in the dome construction. Improving the knowledge about the tridimensional shape and the construction techniques of such dome is of crucial importance at the moment, because the Sanctuary is the subject of a structural monitoring and research campaign due to the important settlements and cracking fenomena that affect the building.